The Subminimum Wage Reform in Greece and the Labour-Labour Substitution Hypothesis - Theano Kakoulidou; Panagiotis Konstantinou; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2018)
The paper examines the effects of the age-differentiated decreases in the minimum wage which Greece implemented in 2012, and which involved the introduction of a subminimum wage as a result of the reduction of the minimum wage by 22% for workers aged 25 and above, and by 32% for those aged less than 25. Using data from the Greek Labor Force Survey, we estimate probit models and find that after the reform there was no statistically significant change in the differential employment probability advantage for private sector employees aged 25-27 over those aged 22-24. We also find that the probability of labour force participation for individuals in the 25-27 group becomes significantly higher (relative to the 22-24 group), which is reflected in a (statistically) significant improvement in the relative job finding rate for non-agricultural, private-sector employees of this group after the reform. Moreover, the reform had no significant differential impact on employment terminations; i.e. it had no differential impact on either dismissals or quits. These findings remain unaltered to a series of robustness checks.
Keywords: J21; J23; J30; 330; minimum wages; sub-minimum reform; employment; Greece